Sub-nanometer Cu(i) clusters: coordination-modulated (Se vs. S) atom-packing mode and emission. Issue 37 (11th September 2019) - Ke, Feng; Song, Yongbo; Li, Hao; Zhou, Chuanjun; Du, Yuanxin; Zhu, Manzhou
Abstract : Different coordination modes of S/Se–Cu significantly modulate the atom-packing mode of Cu(i ) clusters. Abstract : Herein, the ligands' effect in Cu(i ) clusters was initially explored. The results demonstrate that the Se atom possesses more coordination modes with Cu (μ2, μ3, μ4, μ6 ) than S, which significantly modulates the atom-packing mode of Cu(i ) clusters. Importantly, this also endows these clusters with different temperature-dependent luminescent behaviours.